2016
DOI: 10.1038/srep22359
|View full text |Cite
|
Sign up to set email alerts
|

Starving honey bee (Apis mellifera) larvae signal pheromonally to worker bees

Abstract: Cooperative brood care is diagnostic of animal societies. This is particularly true for the advanced social insects, and the honey bee is the best understood of the insect societies. A brood pheromone signaling the presence of larvae in a bee colony has been characterised and well studied, but here we explored whether honey bee larvae actively signal their food needs pheromonally to workers. We show that starving honey bee larvae signal to workers via increased production of the volatile pheromone E-β-ocimene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 41 publications
2
56
0
Order By: Relevance
“…4a; Pearson coefficient = 0.84; P = 0.0059; α = 0.0063; Bonferroni correction). Given that this compound is a familiar brood pheromone that is already known to increase worker visits to cells24, this is a remarkable result. Interestingly, β-ocimene was also consistently one of the most intense peaks observed in the chromatograms of dead brood (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…4a; Pearson coefficient = 0.84; P = 0.0059; α = 0.0063; Bonferroni correction). Given that this compound is a familiar brood pheromone that is already known to increase worker visits to cells24, this is a remarkable result. Interestingly, β-ocimene was also consistently one of the most intense peaks observed in the chromatograms of dead brood (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…5, Table 2). This finding is intriguing for two reasons: 1) β-ocimene has previously been shown to increase the frequency of worker visits to brood24 and 2) an independent study found that a different brood pheromone (brood ester pheromone; BEP) was also significantly more abundant in parasitized brood23. By increasing worker visits to brood cells that should otherwise not require attendance, β-ocimene may attract the attention of bees that can perform HB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Individual esters or ester subsets also have some biological activity (Slessor et al, 2005). Additionally, β-ocimene, a highly volatile component, is emitted by larvae to modulate honey bee behavioural maturation and nursing behaviour (He et al, 2016;Maisonnasse, Lenoir, Beslay, Crauser, & Le Conte, 2010;Traynor, Le Conte, & Page, 2015). These brood signals are mainly perceived by the antennae (Robertson & Wanner, 2006), the central olfactory organ of all insects, in which odourant transduction occurs within a few milliseconds from the boundary layer of the antenna to olfactory receptor neurons (Leal, 2013;Szyszka, Gerkin, Galizia, & Smith, 2014).…”
Section: Introductionmentioning
confidence: 99%